The Role of Pancasila in Education in the Millennial Era - Damayanti, Nina (Journal of Creativity Student, 2018)
Education is the process of giving knowledge to students to develop the potential, ability, and activity of students. With the aim of students developing into humans who fear God, have noble character, are intelligent, and become citizens who are supportive, responsible, also beneficial to their country. In fact, Indonesia has many problems that not only harm individuals who harm many people. Among them are examples of corruption, criminality, terrorism, and many cases related to the case are the moral degradation of Indonesian citizens today, which has greatly reduced the values of Pancasila that cannot be used in their lives. Because the Pancasila is the basis for the Indonesian state which was made as a view of the Indonesian nation, which contains divine values, enjoyment, unity, popularism, prosperity. The early changes of Pancasila must be introduced by a generation of people who will later become the successors of the realization of the ideals of the Indonesian people. Then Pancasila education is needed to shape the character of a generation of people who are pious, noble, intelligent, democratic, and responsible.